Comparison of Hemoglobin Levels in Stunting and Non Stunting Children at State Elementary School 018092 Lobu Rappa - Sarumpaet, Arif Mawardi; Damanik, Rosa Zorayatamin; Ayu, Mayang Sari; Rahmadhani, Mayasari (International Journal of Public Health Excellence (IJPHE), 2025)
Background : In North Sumatra, there is still a high potential for stunting with a stunting prevalence of 21.1 percent. It is assumed that anemia is one of the risk factors for stunting. Not much research has been done regarding the incidence of anemia as a risk factor for stunting. Objective: The purpose of this study was to determine the incidence of anemia in stunting and non-stunting children. Methods: This study uses an observational analytical approach with a cross-sectional design. The sample consists of 30 first-grade elementary school children who meet the inclusion and exclusion criteria. The data analysis used is the Fisher’s Exact Test. Results: The results showed that out of 30 elementary school children measured, there were 11 children with stunting nutritional status, 7 of them have low hemoglobin levels or anemia, while 19 children with non-stunting nutritional status, 3 of them have low hemoglobin levels or anemia with the results of the chi-square statistical test (P=0,015). Conclusion : There were differences in hemoglobin levels in stunted and non-stunted children at SD Negeri 010892 Lobu Rappa.